Therapeutic Potential of Neoechinulins and Their Derivatives: An Overview of the Molecular Mechanisms Behind Pharmacological Activities - Sharifi-Rad, Javad; Bahukhandi, Amit; Dhyani, Praveen; Sati, Priyanka; Capanoglu, Esra; Docea, Anca Oana; Al-Harrasi, Ahmed; Dey, Abhijit; Calina, Daniela (Frontiers in Nutrition, 2021)
Neoechinulins are diketopiperazine type indole alkaloids that demonstrate radical scavenging, anti-inflammatory, antiviral, anti-neurodegenerative, neurotrophic factor-like, anticancer, pro-apoptotic and anti-apoptotic properties. An array of neoechinulins such as neoechinulins A-E, isoechinulins A-C, cryptoechunilin have been isolated from various fungal sources like Aspergillus sp., Xylaria euglossa, Eurotium cristatum, Microsporum sp. etc. Besides, neoechinulin derivatives or stereoisomers were also obtained from diverse non-fungal sources viz. Tinospora sagittata, Opuntia dillenii, Cyrtomium fortunei, Cannabis sativa and so on. The main purpose of this review is to provide an update information on neoechinulins and their analogues about the molecular mechanisms of pharmacological action and possible future research. The recent data from this review can be used to create a basis for the discovery of new neoechinulin-based drugs and their analogues in the near future. The online databases PubMed, Science and Google scholar were researched for the selection and collection of data from the available literature on neoechinulins, their natural sources and their pharmacological properties. The published books on this topic were also analyzed. In vitro and in vivo assays have established the potential of neoechinulin A as a promising anticancer and anti-neuroinflammatory lead molecule. Neoechinulin B was also identified as a potential antiviral drug against hepatitis C virus. Toxicological and clinical trials are needed in the future to improve the phyto-pharmacological profile of neoquinolines. From the analysis of the literature we found that neoechinulins and its derivatives have a special biological biological potential. Although some modern pharmacological analyzes have highlighted the molecular mechanisms of action and some signaling pathways, the correlation between these phytoconstituents and pharmacological activities must be validated in the future by preclinical toxicological and clinical studies.